Law and democracy in Neil MacCormick's legal and political theory the post-sovereign constellation - Menendez, Agustin; Fossum, John; SpringerLink (Online service). (Dordrecht Netherlands Springer, 2011)
This volume offers a collection of articles by leading legal and political theorists. Originally intended as a celebration of MacCormick's work on the occasion of the completion of the four-volume series on Law, State and Practical Reason, it has turned into a homage and salute after MacCormick's passing. Cast in MacCormick's reflexive spirit, the book presents a critical reconstruction of the Scottish philosopher's work, with the aim of revealing the connections between law and democracy in his writings and furthering his insights in each specific field. Neil MacCormick made outstanding contributions to the understanding of law and democracy under conditions of pluralism. His institutional theory of law has elucidated the close connection between the normative character of law as a means of social integration and legal social practices. This has produced a synthesis of the key insights of the legal and political theories of Kelsen, Hart, Alexy and Dworkin, and has broken new ground by undermining the monolithic and nation-state centered character of standard legal theories
Acknowledgements List of Contributors Introduction Part I: A Life in Law and Politics Chapter 1 The Cosmopolitan Local Neil Walker Part II: The Seven Big Themes in Maccormick's Legal and Political Theory Chapter 2 MacCormick on MacCormick D. Neil MacCormick Part III: The Limits of Law Chapter 3 Juridification From Below: The Dynamics of MacCormick's Institutional Theory of Law Lars Christian Blichner Chapter 4 Reform And Tradition: Changes And Continuities in Neil Maccormick's Concept Of Law Massimo La Torre Chapter 5 The Master Rule, Normativity, and The Institutional Theory Of Law Stefano Bertea Part IV: Jurisprudence Chapter 6 Some Reflections on the Relationship between Law and Morality Neil MacCormick's Point Of View Marina Lalatta Costerbosa Chapter 7 Legal Judgment and Moral Reservation Jeremy Waldron Chapter 8 Are We Beyond Sovereignty? The Sovereignty of Processes and the Democratic Legitimacy Of The European Union Tanja Hitzel-Cassagnes Part V: Legal Argumentation Chapter 9 Coherence And Post-Sovereign Legal Argumentation Flavia Carbonell Part VI: The Constitution(S) of the European Union Chapter 10 Legal Pluralism in the European Union Martin Borowski Chapter 11 From Constitutional Pluralism To A Pluralistic Constitution Constitutional Synthesis as a MacCormickian Constitutional Theory of European Integration Agustín José Menéndez Part VII: Post-Sovereign Nationalism Chapter 12 Nation-States Vs. Nation-Regions in The Post-Sovereign European Polity Joxerramon Bengoetxea Chapter 13 Nationalism, Patriotism and Diversity Conceptualising The National Dimension In D. Neil MacCormick's Post-Sovereign Constellation John Erik Fossum
Includes bibliographical references and index
Electronic reproduction
Keywords: MacCormick, Neil; Law -- Philosophy; Political science -- Philosophy